The Effects of Different Antigen–Antibody Pairs on the Results of 20 Min ELISA and 8 Min Chromatographic Paper Test for Quantitative Detection of Acetamiprid in Vegetables - Yuxiang Wu; Yemin Guo; Qingqing Yang; Falan Li; Xia Sun (Biosensors, 2022)
To establish rapid, high-sensitive, quantitative detection of ACP residues in vegetables. A 1G2 cell clone was selected as the most sensitive for anti-ACP antibody production following secondary immunization, cell fusion, and screening. The affinity of the 1G2 antibody to each of the four coating agents (imidacloprid–bovine serum albumin [BSA], thiacloprid–BSA, imidaclothiz–BSA, and ACP-BSA) was determined using a 20 min enzyme-linked immunosorbent assay (ELISA). The half maximal inhibitory concentration (IC50) was 0.51–0.62 ng/mL, showing no significant difference in affinity to different antigens. However, we obtained IC50 values of 0.58 and 1.40 ng/mL on the linear regression lines for 1G2 anti-ACP antibody/imidacloprid–BSA and 1G2 anti-ACP antibody/thiacloprid–BSA, respectively, via quantum dot (QD)-based immunochromatography. That is, the 1G2 antibody/imidacloprid–BSA pair (the best combination) was about three times more sensitive than the 1G2 antibody/thiacloprid–BSA pair in immunochromatographic detection. The best combination was used for the development of an 8 min chromatographic paper test. With simple and convenient sample pretreatment, we achieved an average recovery of 75–117%. The coefficient of variation (CoV) was <25% for all concentrations tested, the false–positive rate was <5%, the false–negative rate was 0%, and the linear range of the method was 50–1800 μg/kg. These performance metrics met the ACP detection standards in China, the European Union (EU), and the United States (US). In summary, in this study, we established an 8 min QD-based immunochromatographic stripe for the rapid and accurate quantitative determination of ACP residues in vegetables.